Nash equilibrium seeking for individual linear dynamics subject to limited communication resources - Liu, Pin; Xiao, Feng; Wei, Bo; Yu, Mei (Systems & control letters, 2022)
In this paper, non-cooperative game problems with individual linear dynamics of players are addressed. In the case of limited communication resources, event-triggering mechanisms equip players to determine event instants. A period of dwell time is enforced after each event. In the dwell time, monitoring event-triggering conditions is avoided for each player, which saves resources. After the dwell time, each player triggers the broadcast to its neighbors once a fully distributed event-triggering condition is satisfied. Along this line, the Zeno behavior is excluded. The proposed control algorithm with discrete-time communications converges the systems to an NE. The effectiveness of the proposed control algorithms and event-triggering mechanisms is demonstrated through simulations.